Safety and Efficacy of the BNT162b2 mRNA Covid-19 Vaccine - Polack, Fernando P. (2021)
Moreira Junior, Edson Duarte. Fundação Oswaldo Cruz. Instituto Gonçalo Moniz. Salvador, BA, Brasil. Fundacion INFANT (F.P.P.) and iTrials-Hospital Militar Central (G.P.M.), Buenos Aires; State University of New York, Upstate Medical University, Syracuse (S.J.T.), and Vaccine Research and Development, Pfizer, Pearl River (J.A., A.G., K.A.S., K.K., W.V.K., D.C., P.R.D., K.U.J., W.C.G.) — both in New York; Vaccine Research and Development, Pfizer, Hurley, United Kingdom (N.K., S.L., R.B.); Vaccine Research and Development (J.L.P., P.L.) and Worldwide Safety, Safety Surveillance and Risk Management (S.M.), Pfizer, Collegeville, PA; Associação Obras Sociais Irmã Dulce and Oswaldo Cruz Foundation, Bahia (E.D.M.), and Centro Paulista de Investigação Clinica, São Paulo (C.Z.) — both in Brazil; Global Product Development, Pfizer, Peapack, NJ (S.R.); Cincinnati Children’s Hospital, Cincinnati (R.W.F.); Johns Hopkins Bloomberg School of Public Health, Baltimore (L.L.H.); BioNTech, Mainz (ÖT., U.Ş.), and Medizentrum Essen Borbeck, Essen (A.S.) — both in Germany; Tiervlei Trial Centre, Karl Bremer Hospital, Cape Town, South Africa (H.N.); Hacettepe University, Ankara, Turkey (S.Ü.); and Worldwide Safety, Safety Surveillance and Risk Management, Pfizer, Groton, CT (D.B.T.).